Identifying disparities in mental illness and well-being across no-risk, risk, and intersectional groups during the Covid-19 pandemic and the role of sociodemographics in mental health outcomes - Cristofthe J. Fernandes; Félix Neto; Patrício Costa (Brazilian Journal of Psychiatry)
Objective: Few pandemic studies have explored positive aspects of mental health employing an intersectional perspective. Our intersectional investigation aimed to identify mental illness and well-being differences between groups identified as psychologically vulnerable during the pandemic by the World Health Organization (immigrants, minorities, and people with psychiatric diagnoses) and people without pre-existing risk factors while controlling for sociodemographic variables. Methods: This cross-sectional survey included 1,134 participants (76.1% women) aged 18 to 76 years. We used the Depression, Anxiety, and Stress Scales to assess mental disorders and the Satisfaction with Life Scale and the Positive and Negative Affect Schedules to assess well-being. Results: Through a variable-centered approach, multivariate analysis revealed significant mental health differences between the groups: depression (F2.1131 = 72.7, p < 0.001), anxiety (F2.1131 = 78.0, p < 0.001), stress (F2.1131 = 85.9, p < 0.001), and subjective well-being (F2.1131 = 53.6, p < 0.001). The groups also differed when a person-centered approach was used to analyze the variables jointly through latent profile analysis. We identified six mental profiles consisting of different levels of depression, anxiety, stress, and well-being. The risk and intersectional groups were more likely to be characterized by the generalized suffering (ORrisk = 0.85, ORintersec = 0.93) and profound anguish (ORrisk&intersec = 0.97) profiles. After controlling for demographic variables, mental health disparities were partially attributed to participant risk conditions. Conclusions: Based on our results, we emphasize the urgent need for public health policies that consider the specificities and vulnerabilities of minority and risk groups.